The effects of Baduanjin exercise vs. brisk walking on physical fitness and cognition in middle-aged patients with schizophrenia: A randomized controlled trial - Chen, Chyi-Rong; Huang, Yu-Chi; Lee, Yi-Wen; Hsieh, Hui-Hsien; Lee, Yi-Chen; Lin, Keh-chung (Frontiers in Psychiatry, 2022)
Objective Patients with schizophrenia have deficits in physical and cognitive function that may become salient in their middle ages. These deficits need active intervention to prevent functional decline. Baduanjin and brisk walking show promise as interventions in patients with schizophrenia. This study investigated the effects of Baduanjin exercise vs. brisk walking in middle-aged patients with schizophrenia. Methods In this single-blind, 2-arm, parallel, randomized controlled trial, 48 participants aged older than 40 years were enrolled and assigned to the intervention group (Baduanjin) or the control group (brisk walking). The training of both groups took place twice a week, 60 min per session, for 12 weeks. The participants were evaluated with physical, cognitive, and functional outcomes at baseline, postintervention, and 4 weeks after the intervention. Results The results of the study demonstrated significant time effects in walking distance (p = 0.035, η2 = 0.094) and lower extremity strength (p = 0.006, η2 = 0.152). Post-hoc analysis revealed both groups had significant improvement in changes from baseline to the postintervention assessment (ps < 0.05) and follow-up (ps < 0.05). The results demonstrated a significant group-by-time interaction in change scores of global cognition (F = 7.01, p = 0.011, η2 = 0.133). Post-hoc analysis revealed a significant improvement in the Baduanjin group from baseline to postintervention (p = 0.021), but the improvements were not maintained at the follow-up assessment (p = 0.070). The results also demonstrated significant group effects in balance function (p < 0.001, η2 = 0.283), motor dual-task performance (p = 0.026, η2 = 0.103), and cognitive dual-task performance (p < 0.001, η2 = 0.307). Post-hoc analysis revealed that the Baduanjin group improved more than the brisk walking group in the above outcomes (ps < 0.05). Conclusion This study demonstrated the differential effects of Baduanjin exercise and brisk walking in middle-aged patients with schizophrenia. Baduanjin might be a beneficial regimen for improving physical and cognitive function in this population. Further research with a larger sample is warranted. Clinical trial registration [ClinicalTrials.gov], identifier [202000817B0C602].